Royalties: looking for a better resources distribution (2016)
General System of Royalties - SGR (Spanish acronym) has contributed positively to reduce development gaps among the regions in Colombia, making the possibility to little towns to have access to resources from of royalties in order to invert on new projects looking for make better the quality of life of population. Topaipí town is a little town that has been beneficed with resources to encourage planning offices, encourage SMSCE (Monitoring, tracing, control and evaluation system) and finances inversion projects in order to make possible the mission of town and comply goals proposals in the Development Plan.